La importancia de la Inteligencia artificial en la toma de decisiones clínicas en medicina. - Matza Aldas, Noemi Monserrath (2024)
Artificial intelligence (AI) has emerged as a transformative force in healthcare, with the potential to revolutionize clinical decision-making and patient care. This systematic review of the literature aims to explore the promising role of AI in improving clinical decision-making, the challenges and opportunities it presents, and how AI can help doctors provide better patient care. This review identifies and analyzes outstanding studies using the rigorous Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. Comprehensive research was conducted in databases such as PubMed, Springer Link, Scopus, and Web of Science using keywords related to AI, clinical decision-making, and medicine. It included published studies between 2019 and 2023, including quantitative and qualitative research on AI applications in clinical settings. The literature reviewed consistently demonstrates AI's potential to significantly improve clinical decision-making in various medical specialties. AI algorithms, including automatic learning and deep learning models, analyze complex data sets to identify patterns, predict outcomes, and provide decision support to healthcare providers. These AI-based tools have the potential to greatly improve diagnostic accuracy, treatment planning, and patient management, thereby enhancing healthcare outcomes and patient satisfaction. Conversely, although AI offers excellent opportunities, it also presents several challenges. These include data privacy, algorithm bias, integration with existing healthcare systems, and the need to validate and monitor AI models continuously. AI-based decision support systems provide real-time insights, evidence-based recommendations, and personalized treatment plans tailored to each patient's needs. It improves the accuracy and efficiency of clinical decisions, allows doctors to focus more on patient interaction and empathy, and provides comprehensive care. In addition, AI enhances the allocation of healthcare resources, reduces medical errors, and contributes to cost-effective healthcare delivery.